Ordered Convex Metric Spaces - Ismat Beg (Journal of Function Spaces)
The aim of this article is to introduce a new notion of ordered convex metric spaces and study some basic properties of these spaces. Several characterizations of these spaces are proven that allow making geometric interpretations of the new concepts.